A Comparative Study of the Antibacterial Effect of Three Ethnomedical Plants (Ocimum gratissimum, Vernonia amygdalina and Cymbopogon citratus) on Certain Clinical Isolates - Obhioze Augustine Akpoka *; Maureen U. Okwu; Odaro Stanley Imade; Spencer C. O. Nwangwu; Erifeta Georgina Omonegho; Christabel Uti (Lorestan University of Medical Sciences, 2019)
Background and Aim: Ethnomedicinal plants are used by indigenous populations all over the world as remedies for various maladies. The present study aimed at evaluating the antibacterial susceptibility of the leaves of Cymbopogon citrates, Vernonia amygdalina and Ocimum gratissimum against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and methicillin-resistant Staphylococcus aureus. Materials and Methods: Active agents in the leaves were extracted with methanol using the Soxhlet extraction technique. The extracts were then tested for antibacterial activity using the agar well diffusion method. MIC was determined by the tube dilution technique. Results: The results revealed that the methanolic extract of C. citrates had the best mean zones of inhibition against P. aeruginosa, S. aureus, E. coli and methicillin-resistant S. aureus. The mean zones of the inhibition of C. citrates against P. aeruginosa, S. aureus, E. coli and methicillin-resistant S. aureus were 11.5 ± 1.5 mm (31.25 mg/ml), 11.5 ± 0.5 mm (125 mg/ml), 12.0 ± 1.0 (125 mg/ml) and 12.0 ± 1.0 (500 mg/ml) respectively. The activities of the extracts in relation to the activity of gentamycin (positive control) and DMSO (negative control) were also determined. The methanolic extract of C. citrates had the highest activity (38 %) against Pseudomonas aeruginosa at 31.25 mg/ml and S. aureus (54%) at 250 mg/ml and (52%) against MRSA at 500 mg/ml. V. amygdalin showed the highest activity (35%) against E. coli at 125 mg/ml. The therapeutic efficacy was also determined using the breakpoint of 10 µg gentamycin (the positive control). Conclusion: The findings of this study suggest that C. citrates, V. amygdalina and O. gratissimum could be explored by pharmaceutical companies as raw materials for the synthesis of new antibiotics for the treatment of bacterial infections, particularly as a cocktail.